2007
DOI: 10.1080/02844310600699457
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell tumour of the finger

Abstract: Merkel cell carcinoma (MCC) is a rare primary neuroendocrine tumour. Biologically aggressive, it may be difficult to treat. We report a case of MCC on the dorsal base of the left second finger and we discuss its treatment and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It has very rarely been described on the fingers or the hand, with only few case reports that we are aware of [3][4][5][6][7][8][9][10][11][12][13][14][15]16]. Because of its rarity and the small numbers of patients in clinical reports, management is not standardized.…”
Section: Discussionmentioning
confidence: 97%
“…It has very rarely been described on the fingers or the hand, with only few case reports that we are aware of [3][4][5][6][7][8][9][10][11][12][13][14][15]16]. Because of its rarity and the small numbers of patients in clinical reports, management is not standardized.…”
Section: Discussionmentioning
confidence: 97%
“…Spalveri et al reported a 2-cm diameter MCC on the dorsum of the proximal phalanx of the index finger treated by wide local excision. The 3.5脳3 cm defect was reconstructed with a retrograde kite flap, and the patient remained disease free 20 months postoperatively [15]. Su et al reported a 4-mm lesion on the ring finger, which was excised, and the sentinel Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the Surveillance, Epidemiology, and End Result (SEER) database reported 1234 (24 %) Merkel cell carcinomas in the hand and upper extremity from 1986 to 2009 [5], there are only 11 case reports of MCC of the digit found in PubMed, Medline, and MD Consult databases [6][7][8][9][10][11][12][13][14][15][16]. Although over a thousand cases were identified in the SEER database, there was no further subdivision of the upper extremity.…”
Section: Introductionmentioning
confidence: 99%
“…Usual presentation of primary MCC is a solitary violet or blue dome-shaped rapidly growing nodule with non-tender intra-cutaneous swelling. The common locations are head and neck (50%), extremities (40%), and trunk (10%) 4 . Finger involvement has been rarely reported.…”
Section: A Case Of Merkel Cell Carcinoma On the Fingermentioning
confidence: 99%
“…But, the known risk factors for MCC are sun exposure, immunosuppression, and Merkel cell polyomavirus infection 1 . Of all cases of MCC, 85% appear in sun exposed sites, so ultraviolet exposure seems to be a significant etiological factor 4 . The occurrence of MCC at the hands and fingers is likely to occur due to exposure to sunlight.…”
Section: A Case Of Merkel Cell Carcinoma On the Fingermentioning
confidence: 99%